2018
DOI: 10.4218/etrij.2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Design of optimum criterion for opportunistic multi-hop routing in cognitive radio networks

Abstract: The instability of operational channels on cognitive radio networks (CRNs), which is due to the stochastic behavior of primary users (PUs), has increased the complexity of the design of the optimal routing criterion (ORC) in CRNs. The exploitation of available opportunities in CRNs, such as the channel diversity, as well as alternative routes provided by the intermediate nodes belonging to routes (internal backup routes) in the route‐cost (or weight) determination, complicate the ORC design. In this paper, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…However, traditional deterministic routing protocols have many limitations in dealing with unstable links [12]. The studies [13][14][15] showed that opportunistic routing strategies are used more and more widely. It makes full use of the broadcast characteristics and has an obvious advantage over traditional routing in solving unreliable links.…”
Section: Related Workmentioning
confidence: 99%
“…However, traditional deterministic routing protocols have many limitations in dealing with unstable links [12]. The studies [13][14][15] showed that opportunistic routing strategies are used more and more widely. It makes full use of the broadcast characteristics and has an obvious advantage over traditional routing in solving unreliable links.…”
Section: Related Workmentioning
confidence: 99%
“…Yousofi et al 23 modeled CRN as same as a multigraph first weight was found depending on PU sender's behavior and PU receivers' protection, with subsequent weight depending on the bandwidth of channel. In the subsequent stage, for CRN an ORC is presented which is mentioned as ETED_BEST.…”
Section: Related Workmentioning
confidence: 99%
“…In [22] the author modeled CRN as same as a multigraph rst weight was found depending on PU sender's behavior and PU receivers' protection, with subsequent weight depending on the bandwidth of channel. In the subsequent stage, for CRN an ORC is presented which is mentioned as ETED_BEST.…”
Section: Related Workmentioning
confidence: 99%